AB0875 Complex Assessment of Elderly Patients with Uncomplicated Mechanical Low Back Pain. (10th June 2014) - Traistaru, R.M.; Popescu, R.; Matei, D.; Kamal, D.
Abstract : Background: The prevalence of uncomplicated mechanical low back pain (LBP) in the elderly people is estimated to be more than 75%. This entity generates disability and quality of life disturbances. So, any elderly patient with a first accuse of low back requires complex evaluation. Objectives: We completely assessed the uncomplicated mechanical LBP elderly patients and evaluated the correlation between ultrasound thickness difference in three different trunk postures and functional parameters. Methods: 48 elderly patients with LBP were enrolled in our observational study. Frontal (AP) and lateral lumbosacral regions were radiological evaluated. Clinical and functional parameters were collected by a physiotherapist and an ultrasound (US) examination was performed by a physiatrist within 72 hours of the clinical examination. We measured the thickness of the erector spinal muscles at L4 and L5 level in maximum flexion, neutral posture, and maximum extension. Results: Multivariate analysis showed that thickness differences between flexed and neutral, and flexed and extended maximally positions were correlated statistically with functional parameters (The Roland-Morris Disability Questionnaire score). Conclusions: LBP is more likely to arise in correlation with the erector vertebral muscle status. Visual observation of the image during contraction indicates that US may be a valuable biofeedback tool. The relationship between musculoskeletal status and back pain represents an important factor for the therapeutic measures. Change of lifestyle, and rehabilitation program to alleviate pain and stiffness are measures that might improve quality of life. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1531